Foreign Language Proficiency and Learning Strategies of Souvenir Peddlers in the Borobudur Temple Area - Rachman, Zulfikar; Muhammad Reza Rustam (Chi e Journal of Japanese Learning and Teaching, 2025)
This study examines the foreign language proficiency and learning experiences of souvenir peddlers around the Borobudur Temple area. The study has two main objectives: (1) to explore the background of the peddlers and (2) to analyze their foreign language skills and acquisition methods. Using a qualitative descriptive approach, data were collected through questionnaires and interviews with five souvenir peddlers aged 39-58 with varying educational backgrounds. Findings reveal that these peddlers can communicate in multiple foreign languages, including English, Japanese, Chinese, French, Korean, Dutch, German, Thai, Malay, Spanish, and Italian. However, their language acquisition occurs informally, primarly through interactions with tourists rather than formal education or textbooks. While some began learning languages at a young age, others started only after entering the souvenir trade. The study highlights the role of necessity and direct exposure in shaping language proficiency. The results suggest that foreign language skills significantly impact the peddlers’ ability to engage with international tourists and enhance sales opportunities. Future research should expand to other tourist destinations, such as Bali, Lombok, and Labuan Bajo, to compare language acquisition patterns among souvenir vendors in different regions.